2020
DOI: 10.1038/s41390-020-0841-6
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive optical measurement of microvascular cerebral hemodynamics and autoregulation in the neonatal ECMO patient

Abstract: Background Extra-Corporeal Membrane Oxygenation (ECMO) is a life-saving intervention for severe respiratory and cardiac diseases. However, 50% of survivors have abnormal neurologic exams. Current ECMO management is guided by systemic metrics, which may poorly predict cerebral perfusion. Continuous optical monitoring of cerebral hemodynamics during ECMO holds potential to detect risk factors of brain injury such as impaired cerebrovascular autoregulation ( CA ). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…The finding of contradictory decrease in PVD after increasing VA-EMCO pump flow is compatible with that of Busch et al (31). They suggest that cerebral blood flow and oxygenation are not well-predicted by VA-ECMO pump flow or blood pressure.…”
Section: Discussionsupporting
confidence: 89%
“…The finding of contradictory decrease in PVD after increasing VA-EMCO pump flow is compatible with that of Busch et al (31). They suggest that cerebral blood flow and oxygenation are not well-predicted by VA-ECMO pump flow or blood pressure.…”
Section: Discussionsupporting
confidence: 89%
“…In this overall context, CA impairment in critically ill patients treated by ECMO may be a key factor in the genesis of neurological complications. Recent preliminary studies using different methods have suggested an association with CA disorders and neurological outcome among children supported by ECMO (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of optical intrinsic signals, the scattering changes measured in vivo for profound physiological perturbation (e.g., middle cerebral artery occlusion stroke model) are <5%. 62 Other causes of dramatic scattering change, e.g., edema, 65 have little effect on the time scale of this measurement. Given these findings, it seems reasonable to assume that scattering changes would be highly unlikely to influence the apparent BFI signals.…”
Section: Discussionmentioning
confidence: 97%